Expression of receptor tyrosine kinase targets PDGFR‐β, VEGFR2 and KIT in canine transitional cell carcinoma. (8th September 2017) - Walters, L.; Martin, O.; Price, J.; Sula, M. M.
Abstract : Transitional cell carcinoma (TCC) is the most common neoplasia of the canine urinary tract. It tends to be locally invasive and has a moderate metastatic rate. Receptor tyrosine kinases (RTKs) play an important role in promoting cell growth, differentiation and regulation of cell function. RTK inhibitor toceranib phosphate has been used anecdotally to treat TCC. The goal of this study was to evaluate archived normal urinary bladder, TCC and cystitis bladder samples for expression of toceranib phosphate targets: VEGFR2, PDGFR‐β and stem cell factor receptor (KIT). A significant number of TCC samples expressed PDGFR‐β compared with cystitis and normal bladder samples ( P <.0001). While all the tumour samples stained positively for VEGFR2, there was no significant difference between tumour, cystitis and normal bladder samples in intensity scores or staining distribution. Minimal positive staining for KIT was noted in the tumour samples. Based on this proof of target study, further investigation is warranted to determine clinical response of TCC to toceranib phosphate.